Optimum Commodity Taxation with a Non-Renewable Resource - Julien Daubanes; Pierre Lasserre (Center for Economic Studies and ifo Institute (CESifo), 2015)
Under standard assumptions, optimum commodity taxation (OCT) should target non-renewable resources (NRRs) in priority. NRRs should be taxed at a higher rate than otherwise-identical conventional commodities. NRR substitutes and complements should receive a particular tax treatment. When reserves are endogenous, OCT for NRRs distorts both developed reserves, which are reduced, and their depletion, which is slowed down. Reserves are a form of capital and royalties tax its income: our results contradict Chamley's conclusion that capital should not be taxed in the long run. In a NRR-importing economy, Ramsey taxes are further increased because they allow the capture of foreign rents.
Keywords: Q31; Q38; H21; 330; optimum commodity taxation; inverse elasticity rule; non-renewable resources; Hotelling resource; supply elasticity; demand elasticity; capital income taxation